Alloying of austenitic steel surface with zirconium using nitrogen compression plasma flow. (May 2015) - Sari, A.H.; Astashynski, V.M.; Kostyukevich, E.A.; Uglov, V.V.; Cherenda, N.N.
Abstract: In this study, the effect of a nitrogen compression plasma flow on the microstructural and mechanical properties, as well as on the elemental and phase compositions of a Zr/chromium–nickel steel system has been investigated. The Zr/steel system was exposed to a single pulse of the compression plasma flow or to a series of pulses. The samples were characterized by scanning electron microscopy, Auger electron spectroscopy, X-ray diffraction, and energy dispersive X-ray analyses, and subjected to a Vickers microhardness test. The findings showed the formation of a surface modified layer alloyed by Zr with the thickness of up to ∼12 μm. The modified layer contains α- and γ-iron-based solid solutions, the Fe23 Zr6 intermetallic compound, and ZrN and Cr2 N nitrides due to nitrogen diffusion. The microhardness of the modified layer increased by a factor of ∼2. Highlights: Austenitic steel surface layer was alloyed by Zr up to a depth of ∼12 μm. Surface nitriding and Zr alloying occur by nitrogen compression plasma flows. Steel surface contains α- and γ-iron-based solid solutions, Fe23 Zr6, and Cr2 N. A composite thin film containing ZrN exists on the steel surface. The surface microhardness increased by a factor of ∼2.